Non-spatial impairments affect false-positive neglect diagnosis based on cancellation tasks - Huygelier, H; Moore, MJ; Demeyere, N; Gillebert, CR (Cambridge University Press, 2020)
Objective: To diagnose egocentric neglect after stroke, the spatial bias of performance on cancellation tasks is typically compared to a single cutoff. This standard procedure relies on the assumption that the measurement error of cancellation performance does not depend on non-spatial impairments affecting the total number of cancelled targets. Here we assessed the impact of this assumption on false-positive diagnoses.